(MBSE)2: Using MBSE to Architect and Implement the MBSE System. Issue 1 (30th September 2020) - Noguchi, Ryan A.; Martin, James N.; Wheaton, Marilee J.
Abstract: Model‐Based Systems Engineering (MBSE) is being applied in a new way at the enterprise level for the benefit of all its major programs and business units. For an enterprise to successfully implement MBSE, it must integrate models, datasets, tools, and infrastructure with appropriate processes, methods, and standards into a comprehensive, integrated MBSE "System". This paper describes an approach being put to practice, which leverages MBSE principles and methods to architect this MBSE System, focusing on the descriptive models that serve as the foundation for MBSE. The approach is named (MBSE) 2 since it uses MBSE to architect and implement the MBSE System. This (MBSE) 2 approach is illustrated with example models of the MBSE System, showing how these models are used to inform the architecting process, monitor agile implementation of models, and facilitate model‐based execution of SE reviews and audits. Summary For an enterprise to successfully implement MBSE, it must integrate models, datasets, tools, and infrastructure with appropriate processes, methods, and standards into a comprehensive, integrated MBSE System. This paper describes an approach that uses system architecting and MBSE principles and methods to architect this MBSE System, focusing on the descriptive models that serve as the foundation for MBSE. The approach has been named (MBSE) 2 since it uses MBSE to architect and implement the MBSE System. This (MBSE) 2 approach was illustrated with example models of the MBSE System, showing how system modeling tools can be used to analyze the MBSE System models to inform the architecting process, monitor the agile implementation of models, and facilitate the evolved execution of SE reviews and audits.